Bulk changes in the microhardness of a solid WC-110G13 steel alloy exposed to a low-energy, high-current electron beam; Technical Physics Letters; Vol. 25, iss. 10 - Gnyusov S. F. Sergey Fedorovich; Ivanov Yu. F. Yuriy Fedorovich; Proskurovski D. I.; Rotshtein V. P. (1999, 1999)
Title screen